2004
DOI: 10.1038/ni1031
|View full text |Cite
|
Sign up to set email alerts
|

Altered somatic hypermutation and reduced class-switch recombination in exonuclease 1–mutant mice

Abstract: The generation of protective antibodies requires somatic hypermutation (SHM) and class-switch recombination (CSR) of immunoglobulin genes. Here we show that mice mutant for exonuclease 1 (Exo1), which participates in DNA mismatch repair (MMR), have decreased CSR and changes in the characteristics of SHM similar to those previously observed in mice mutant for the MMR protein Msh2. Exo1 is thus the first exonuclease shown to be involved in SHM and CSR. The phenotype of Exo1(-/-) mice and the finding that Exo1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
188
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(200 citation statements)
references
References 49 publications
10
188
1
1
Order By: Relevance
“…Mice deficient in the MutL homologs Mlh1 and Pms2 have altered SHM and CSR patterns (13)(14)(15)(16)(17)(18)(19)(20). Exonuclease 1-mutant mice have altered SHM and reduced CSR (21). Interestingly, mice deficient in Mlh3 have increased SHM, suggesting that Mlh3 normally reduces the SHM mutation load (22).…”
Section: Somatic Hypermutation and Class Switch Recombination Inmentioning
confidence: 98%
“…Mice deficient in the MutL homologs Mlh1 and Pms2 have altered SHM and CSR patterns (13)(14)(15)(16)(17)(18)(19)(20). Exonuclease 1-mutant mice have altered SHM and reduced CSR (21). Interestingly, mice deficient in Mlh3 have increased SHM, suggesting that Mlh3 normally reduces the SHM mutation load (22).…”
Section: Somatic Hypermutation and Class Switch Recombination Inmentioning
confidence: 98%
“…4). By contrast, MSH2 deficiency results in a decreased mutagenesis at A/T bases, a phenotype that is also associated with MSH6 and Exo1 deficiency [100][101][102][103] (but which is not observed in the absence of PMS2 or MLH1, the effector partners of the mismatch repair complex) 42,104 . These contrasting phenotypes led to the proposition of two alternative phases of SHM: one mediated by UNG and generating mutations at G/C bases after uracil excision, and one mediated by MSH2-MSH6, introducing A/T mutations 98 .…”
Section: Ung Msh2 and The A/t Mutagenesis Pathwaymentioning
confidence: 98%
“…If this complex is absent, UNG will process most of the uracils and repair them error free. In wild-type cells, the MSH2-MSH6 complex recruits Exo1 103 , to excise a patch of DNA from a single-strand nick, the origin of which is yet unknown, as well as Polη, which results in mutagenic synthesis of the strand targeted by AID.…”
Section: A Model For Shm: Two Competitive Rather Than Alternative Patmentioning
confidence: 99%
“…These translesion polymerases associate preferentially with monoubiquitylated PCNA. Mouse genetic experiments clearly demonstrated that SHM requires, in addition to MSH2 [50], MSH6 [51], EXO1 [52] and polymerase-η [53,54] also mono-ubiquitylated PCNA [55]. As SHM mutations at T/A base pairs are reduced to a similar extent in knock-in mice expressing a non-ubiquitylatable PCNA K164R variant, and in Msh2 -/-or Msh6 -/-animals [55], the origin of the mutations appears to be monoubiquitylated PCNA-mediated recruitment of error-prone DNA polymerases to MMR-generated gaps (see for [56] recent review).…”
Section: Mmr Proteins In Antibody Maturationmentioning
confidence: 99%